An SCN1A gene missense variant in a Chinese Tujia ethnic family with genetic epilepsy with febrile seizures plus - Li, Ling; Yuan, Lamei; Zheng, Wen; Yang, Yan; Deng, Xiong; Song, Zhi; Deng, Hao (Frontiers in Neurology, 2023)
Genetic epilepsy with febrile seizures plus (GEFSP) is a familial epileptic syndrome that is genetically heterogeneous and inherited in an autosomal dominant form in most cases. To date, at least seven genes have been reported to associate with GEFSP. This study aimed to identify the disease-causing variant in a Chinese Tujia ethnic family with GEFSP by using whole exome sequencing, Sanger sequencing, and in silico prediction. A heterozygous missense variant c.5725A>G (p.T1909A) was identified in the sodium voltage-gated channel alpha subunit 1 gene (SCN1A) coding region. The variant co-segregated with the GEFSP phenotype in this family and it was predicted as disease-causing by multiple in silico programs, which was proposed as the genetic cause of GEFSP, further genetically diagnosed as GEFSP2.These findings expand the genetic and phenotypic spectrum of GEFSP and should contribute to genetic diagnoses, personalized therapies, and prognoses.